Kedudukan Kejaksaan Sebagai Pelaksana Kekuasaan Negara Di Bidnag Penuntutan Dalam Struktur Ketatanegaraan Indonesia - Winda Hamidah; Leliya Leliya; Mabruri Andatu (Hukum, 2026)
The Prosecutor’s Office occupies a distinctive position as a government institution exercising state authority in prosecution while performing functions related to judicial power. This institutional arrangement raises questions concerning prosecutorial independence and accountability within Indonesia’s constitutional structure. This study examines the constitutional position of the Prosecutor’s Office, the adequacy of safeguards for prosecutorial independence, and an appropriate accountability model following the amendment to the Prosecutor’s Office Law, Constitutional Court Decision Number 6/PUU-XXII/2024, and the enactment of the 2025 Criminal Procedure Code. It employs normative legal research using statutory, conceptual, historical, case, and comparative approaches. Legal materials were qualitatively analyzed through grammatical, systematic, historical, and teleological interpretation. The findings demonstrate that Law Number 11 of 2021 strengthened the institutional basis for the independent exercise of prosecutorial functions, while the Constitutional Court decision reinforced the political neutrality required of the Attorney General. The 2025 Criminal Procedure Code further strengthens the public prosecutor’s role as the controller of criminal proceedings under the principle of dominus litis. Nevertheless, prosecutorial independence remains affected by the appointment and dismissal of the Attorney General, hierarchical instructions, career management, conflicts of interest, and organizational culture. The study concludes that the most realistic model is to retain the Prosecutor’s Office as a government institution while strengthening its functional independence through transparent instructions, a merit-based career system, publicly accountable prosecution guidelines, and multilayered oversight.